A taxonomic revision of the spider genus Meriola Banks (Araneae: Trachelidae) - Márquez, María E. González; Grismado, Cristian J.; Ramírez, Martín J. (Zootaxa, 2021)
The genus Meriola Banks currently includes 24 known species of spiders distributed across America, especially in southern South America. They have a nearly straight and narrower posterior eye row compared to other American genera of Trachelidae, and elongated and sharply tipped ventral leg cuspules. The study of specimens of Meriola available in collections revealed two undescribed species, M. avalosi sp. nov. and M. peras sp. nov., and the previously unknown females of M. balcarce Platnick & Ewing and M. quilicura Platnick & Ewing, all of which are described here. The female of M. lineolata (Mello-Leitão) comb. nov., transferred from Cetonana Strand, is described for the first time. Two further new combinations are proposed here: M. macrocephala (Nicolet) comb. nov., transferred from Trachelopachys Simon, and M. setosa (Simon) comb. nov., transferred from Cetonana; these two species are also considered senior synonyms of M. barrosi (Mello-Leitão) and M. hyltonae (Mello-Leitão), respectively. Additionally, a new sex matching of M. ramirezi Platnick & Ewing and M. davidi Grismado is proposed, with a redescription of the female of M. ramirezi provided. New geographical records are provided for all of the species, with images and a revised diagnosis for the genus and the previously known species.